Susceptibility Status of Malaria Vectors to Pyrethroids in Southern Gombe, Northeastern Nigeria - Abba, Ezra; Micah Sale, Pukuma; Adeogun, Adedapo; Poloma Yoriyo, Kennedy; Bala Shuaibu, Abdulmalik; Philimon, Jacob; Augustine, Linda (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The study was conducted to assess the susceptibility of malaria vectors to pyrethroids in four communities from Billiri and Balanga LGAs of Southern Gombe. Four pyrethroid insecticides approved by World Health Organization (WHO) for vector control were used. Anopheles larvae were collected from Kentengereng, Awai, Putoki and Talasse and reared to adults. Two to three-days old, non-engorged female mosquitoes were exposed to the discriminating dosages of 0.05% alphacypermethrin, 0.05% lambdacyhalothrin, 0.05% deltamethrin and 0.75% permethrin susceptibility test kits. Knockdown effect was recorded every 10 min and mortality scored 24 h post-exposure. The mosquito species were morphologically identified. The study revealed that the malaria vectors were susceptible to lambdacyhalothrin (mortality rate between 3% and 74%) except in Talasse where resistance is suspected with mortality upto 97%. Mosquitoes subjected to deltamethrin in Kentengereng were suspected to be resistant with mortality rate of 96% while the other communities were susceptible. Also, susceptibility to alphacypermethrin and permethrin were observed to be susceptible in all the communities. This study revealed a great diversity of malaria vectors and variation in status of susceptibility between the species. This calls for a continued monitoring of resistance status of these mosquitoes for informed policy decision on malaria vector control.